KEEFEKTIFAN PERMAINAN ULAR TANGGA DENGAN MODEL PEMBELAJARAN INQUIRY DALAM PENINGKATAN PEMAHAMAN MATERI PERATURAN LALU LINTAS PESERTA DIDIK KELAS 4 SDN PENGKOL 01 SUKOHARJO - Zakiyyah, Hana; Purwati, Ida; Zulaeha, Ida (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to examine the effectiveness of an inquiry-based snakes and ladders game in improving fourth-grade students' understanding of traffic rules at SDN Pengkol 01 Sukoharjo. The research employed a mixed-method approach with a one-group pretest-posttest design. The instruments used included tests, observation sheets, interviews, and documentation. Data were analyzed using normality and homogeneity tests, t-tests, and N-gain analysis. The results showed a significant increase in the average score from the pretest (65.3) to the posttest (88.6), with a gain of 23.3 points. The t-test analysis yielded a significance value of 0.0000135 < 0.05, indicating a statistically significant difference before and after the implementation of the inquiry-based snakes and ladders game. Moreover, the N-gain test revealed an effectiveness rate of 64.32%, which falls into the moderate category. These findings recommend the use of inquiry-based snakes and ladders games as an effective instructional innovation to enhance student engagement and understanding at the elementary school level.